Peran Kaizen Costing Sebagai Metode Untuk Mengurangi Biaya Produksi Guna Meningkatkan Laba Pada Usaha Tempe Pak Andik Nganjuk - Dewi Laura Fawa’id; Eni Srihastuti; Agus Athori (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
This study aims to determine the role of kaizen costing as a method for reducing production costs in order to increase profits in Pak Andik Nganjuk's tempeh business. This type of research uses quantitative methods. Source of data used is primary data. The data is in the form of reports on production costs, number of employees, company profit and loss statements, production plans and their realization for 2022. Data collection was carried out using interviews and documentation methods.From the results of research that has been done that the application of the Kaizen Costing method and activity analysis by reducing the costs of inefficient activities such as depreciation of production sites but not reducing the number of existing units can optimize the profit percentage of the company by 11 percent. Using the Kaizen Costing method can increase a company's profit, this is evidenced by the gross profit before Kaizen Costing of Rp. 36,000,000 and gross profit after using the Kaizen Costing method of Rp. 40,620,000.